2006
DOI: 10.1097/01.gim.0000245573.42908.34
|View full text |Cite
|
Sign up to set email alerts
|

Reliable detection of Trisomy 21 using MALDI-TOF mass spectrometry

Abstract: Purpose: Current diagnostic methods for chromosomal abnormalities rely mainly on karyotyping and occasionally fluorescent in situ hybridization or quantitative polymerase chain reaction . We describe an alternative molecular method for the detection of trisomy 21 involving mass spectrometric analysis of single nucleotide polymorphisms.Methods: In collaboration with Sequenom, Inc., 350 blinded amniotic fluid, amniocyte culture, chorionic villus, or amniotic fluid supernatant samples were analyzed for trisomy 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…With no false-positive or falsenegative results using more 'user-friendly' assays, the group recommended the approach as an alternative tool for prenatal diagnosis of trisomy 21; the approach is faster and more simple, and it has a high-throughput capacity compared to the conventional methods. To apply the approach for clinical use, our group performed a large-scale study on a cohort with 350 subjects [86]. Again, our data suggested that MALDI-TOF MS is a robust and reproducible method for the detection of trisomy 21.…”
Section: Maldi-tof Ms In Prenatal Diagnosis Of Chromosomal Aneuploidymentioning
confidence: 91%
“…With no false-positive or falsenegative results using more 'user-friendly' assays, the group recommended the approach as an alternative tool for prenatal diagnosis of trisomy 21; the approach is faster and more simple, and it has a high-throughput capacity compared to the conventional methods. To apply the approach for clinical use, our group performed a large-scale study on a cohort with 350 subjects [86]. Again, our data suggested that MALDI-TOF MS is a robust and reproducible method for the detection of trisomy 21.…”
Section: Maldi-tof Ms In Prenatal Diagnosis Of Chromosomal Aneuploidymentioning
confidence: 91%
“…92 The authors pointed out the limitation that the developed method relied on a group of preselected sites, so that it cannot comprehensively detect the highly random mutational patterns in tumor suppressors. 92 MALDI-TOF MS-based nucleic acid analysis has also been applied in genetic diseases, such as trisomy 21 (Down syndrome), a genetic disorder caused by the presence of all or part of the third copy of chromosome 21, 93 genetic deafness inherited from parental generation with genetic and chromosomal abnormalities, 94 and familial adenomatous polyposis (FAP) caused by APC germline mutations, an autosomal dominant colorectal cancer susceptibility syndrome. 97 RNA was extracted from clinical oropharyngeal swabs.…”
Section: Analysis Of Nucleic Acids With Maldi-tof Msmentioning
confidence: 99%
“…The iPLEX assay is a multiplexed singlebase extension assay that generates allele-specific products for detection by MALDI-TOF mass spectrometry. Although originally designed for SNP analysis, the assay has also been used for detecting trisomy (2)(3)(4), as well as high-throughput validation of CNVs (5,6 ). Therefore, the iPLEX assay has potential for integrated high-throughput joint analyses of SNPs and CNVs.…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%